PENTINGNYA PENDIDIKAN KARAKTER DI PERGURUAN TINGGI - Detty Andani; Hasnah Kusumawardani; Selly Mayang Sari; Rabbiatul Alawiyah (JURNAL ILMIAH NUSANTARA, 2025)
Character education is a crucial aspect in shaping the personality and integrity of university students. In the context of globalization and rapid technological advancement, the moral and social challenges faced by the younger generation are becoming increasingly complex. Therefore, higher education institutions are not only responsible for the intellectual development of students, but also for shaping character based on ethical values, social responsibility, and leadership. This article discusses the urgency of integrating character education into the higher education curriculum, effective implementation strategies, and the role of lecturers and institutions in instilling character values in students. Through a holistic and sustainable approach, character education is expected to produce graduates who are not only academically competent but also possess high moral integrity and contribute positively to society.